Differences in student blood pressure before and after consuming fish oil - Nagadi, Eddie; Haroen, Edeh Roletta; Richata, Tuty Sutini (Padjadjaran Journal of Dentistry, 2010)
Introducion: Fish oil is especially believed to be able to decrease blood pressure. This is caused by omega-3 fatty acid that contained in fish oil. This study was implemented to analyzed the difference in student’s blood pressure before and after consuming fish oil. Methods: This study was performed as an experimental research, using pair measurement of the effect of fish oil on blood pressure before and after consuming fish oil. The samples were 30 students aged 18 – 25 years old in Faculty of Dentistry, UNPAD. The amount of fish oil that had to consume were 4 grams per day. Blood pressure measured by the auscultatory-palpation method. Results: The average difference in systolic pressure before and after consuming fish oil is -5,7111 mmHg, while that for diastolic pressure is -4,0889 mmHg. Statistical analysis t-test student with α = 0.05, shows that the value of t for systolic pressure is -12,9389, while that for diastolic pressure is -7,5184. Conclusion: There is differences of blood pressure before and after consuming fish oil. Blood pressure after eating fish oil is lower than before eating fish oil.